Embedded Absorption: The Institutionalization Logic of Urban Community Governance Communities: A Case Study of the"Shared Stairwells" in Ningbo's C Community - Tang, Tianyi (International Journal of Social Sciences and Public Administration, 2026)
The institutionalization of urban community governance communities is key to unlocking fragmented grassroots governance and activating residents' endogenous motivation for participation. While there has been ample policy discourse and diverse practices concerning the construction of urban community governance communities, the internal “institutionalization” mechanism remains a theoretical “black box” that has yet to be fully unpacked. This study argues that “embedded absorption” effectively addresses challenges such as fragmented actors, structural rigidity, and unsustainable actions in community governance through mutual shaping and coordination across three dimensions: actors, structures, and actions. The research reveals that the essence of governance communities lies in the reproduction of social relations, and their institutionalization pathway illustrates a form of creative integration between the state and society within the field of grassroots governance.